DETERMINATION OF ANTIMICROBIAL ACTIVITY OF EXTRACTS OF ENDOPHYTIC FUNGI ISOLATED FROM THE ROOTS OF CYNARA SCOLYMUS L GROWING IN THE UZBEKSITON REGION (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
Today, the increasing need for antibiotics is the reason to search for new sources of antibiotics and conduct research on them. We think that endophytic fungi living in symbiosis with plants serve as a natural source of antibiotic substances.